Broad support for climate action in the EU - Peter Andre; Angelina Hackmann (Leibniz Institute for Financial Research SAFE, 2024)
This paper shows that support for climate action is high across survey participants from all EU countries in three dimensions: (1) Participants are willing to contribute personally to combating climate change, (2) they approve of pro-climate social norms, and (3) they demand government action. In addition, there is a significant perception gap where individuals underestimate others' willingness to contribute to climate action by over 10 percentage points, influencing their own willingness to act. Policymakers should recognize the broad support for climate action among European citizens and communicate this effectively to counteract the vocal minority opposed to it.
Keywords: 330; Climate Change; Climate Behavior; Climate Policies; Social Norms